PENGARUH TATA KELOLA DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN TANGGUNG JAWAB SOSIAL PERUSAHAAN SEBAGAI VARIABEL MODERASI - Youdisanita Lering, Gabriela; Muslichah, Muslichah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the effect of governance and financial performance on company value with corporate social responsibility as a moderating variable. The population in this study were 30 food and beverage manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used the purposive sampling method, with a sample of 17 companies. The research method used was quantitative causal with data sources in the form of secondary data listed on the Indonesia Stock Exchange. The results of the study produced 4 important findings. First, governance has a significant effect on company value, Second, financial performance has a significant effect on company value, Third, social responsibility strengthens the influence of governance on company value. Fourth, social responsibility strengthens the influence of financial performance on company value.